النقابات الصحفية ودورها في إثراء المنظومة التشريعية والإعلامية في الجزائر - • ضريف دلال; د. فيصل بيبي (جامعة محمد بوضياف -المسيلة, 2024)
تشكل النقابات الصحفية آلية من آليات التنظيم الذاتي في الإعلام. وتسعى هذه الدراسة إلى تبيان مناحي دور النقابات الصحفية المهنية في إثراء المنظومة التشريعية والمهنية في وسائل الإعلام الجزائرية. و مدى حضورها مهنيا في تأسيس الفعل النقابي الصحفي.وخلصت إلى وجود غياب مهني في الأدوار والحضور نتيجة المشاكل التي تتخبط فيها الصحافة الجزائرية الكلمات المفتاحية: النقابات الصحفية، الإعلام الجزائري.المنظومة التشريعية (وتضم جمعيات صحفية أوتوماتيكية من التنظيم الذاتي في الإعلام. Press unions constitute a mechanism for self-regulation in the media. This studyseeks to clarify the aspects of the role of professionalpress unions in enriching the legislative and professional system in the Algerian media. And the extent of itsprofessionalpresence in establishingjournalistic union action. It concludedthatthereis a professional absence in roles and attendance as a result of the problems in which the Algerian pressisfloundering Keywords:press unions, Algerian media. The legislative system (whichincludesautomatic self-regulatingpress associations in the media.